Glimpses into Byzantine Philosophy and Art - Vicelja-Matijašić, Marina (IKON, 2022)
Abstract Elena Ene D-Vasilescu, Michelangelo, the Byzantines and Plato, Independent Publishing Network, Oxford, 2021, 116 pp, ISBN 978-180049-879-2 Elena Ene D-Vasilescu, Creation and Time. Byzantine and Modern, Independent Publishing Network, Oxford, 2021, 178 pp, ISBN 978-80049-881-5 Elena Ene D-Vasilescu, Glimpses into Byzantium. Its Philosophy and Arts, Independent Publishing Network, Oxford, 2021, 159 pp, ISBN 978-80049-880-8